The Acquisition of Subject-Verb Agreement in Typically Developing Children: A Corpus-Driven Analysis - Марван Джаррах; Екаб Аль-Шавашрех; Мохаммад Абушарія (Психолінгвістика, 2025)
Purpose. This study investigates the acquisition of subject-verb agreement in Jordanian Arabic (JA) in children aged 2.6 to 12 years, aiming to identify the developmental stages and factors influencing this aspect of language acquisition.